1987
DOI: 10.1016/0042-6822(87)90142-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of the glycoprotein E2 of coronavirus MHV-A59 and identification of the trypsin cleavage site

Abstract: The nucleotide sequence of the peplomer (EZ) gene of MHV-A59 was determined from a set of overlapping cDNA clones. The E2 gene encodes a protein of 1324 amino acids including a hydrophobic signal peptide. A second large hydrophobic domain is found near the COOH terminus and probably represents the membrane anchor. Twenty glycosylation sites are predicted. Cleavage of the E2 protein results in two different 90K species, 90A and 906 (L. S. Sturman, C. S. Ricard, and K. V. 1. Viral 56, 904-91 l), and activates c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
0
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(164 citation statements)
references
References 54 publications
6
157
0
1
Order By: Relevance
“…In addition, the S2 subunit of MHV appeared to play an important role in the cell fusion activity (19, 26 -28, 52, 57). Nevertheless, the amino terminus of MHV S2 subunit does not have the hydrophobic characteristics of those adjoining the cleavage sites of the orthomyxovirus HA and paramyxovirus F glycoprotein (22,58,59). A putative fusogenic peptide (PEP1) in the longer heptad repeat of the S2 subunit of MHV-A59 was recently identified that possibly functions as an internal fusion peptide (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the S2 subunit of MHV appeared to play an important role in the cell fusion activity (19, 26 -28, 52, 57). Nevertheless, the amino terminus of MHV S2 subunit does not have the hydrophobic characteristics of those adjoining the cleavage sites of the orthomyxovirus HA and paramyxovirus F glycoprotein (22,58,59). A putative fusogenic peptide (PEP1) in the longer heptad repeat of the S2 subunit of MHV-A59 was recently identified that possibly functions as an internal fusion peptide (60).…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic cleavage of the S protein precursor into the S1 and S2 subunits was thought to be a prerequisite for the virus to induce cell fusion (14); cell fusion activity correlated with the cleavage level of S protein. The cleavage site was located at the C terminus of the amino acid sequence RRARR in the middle of the S protein (22). Nevertheless, mutations at the cleavage site did not completely abolish the cell fusion activity (23)(24)(25)(26).…”
Section: Mouse Hepatitis Virus (Mhv)mentioning
confidence: 99%
“…Immediately upstream from the first initiation codon there is a sequence ATCTAAACAT very similar to the conserved intergenic sequences of BECV, MHV-JHM and MHV-A59 (Lapps et al, 1987;Cruci+re & Laporte, 1988;Luytjes et al, 1987;Schmidt et al, 1987); it is also closely related to the conserved sequence AACTAAAC, reported for the transmissible gastroenteritis virus (TGEV) (Rasschaert & Laude, 1987). The sequence surrounding the translation initiation codon is in a suboptimal environment (Kozak, 1987).…”
mentioning
confidence: 99%
“…1 b). Luytjes et al (1987Luytjes et al ( , 1988 put forward two hypotheses to account for the difference between MHV-A59 and MHV-JHM in this domain of the S protein. The first hypothesis is that the MHV-JHM genome is deleted with respect to a nucleotide sequence corresponding to amino acids 453 to 545 of the S protein of MHV-A59; the second is that the MHV-A59 genome has acquired genomic material by non-homologous recombination.…”
Section: Llafnqdgvifnavdcksdfmseikcktlsiapstgvyel310mentioning
confidence: 99%
“…To date, no antigenic determinants for any coronavirus E2 protein have been mapped to specific E2 gene sequences, although this gene from several coronaviruses has been sequenced and MAbs have been produced (Binns et al, 1985;Schmidt et al, 1987;Luytjes et al, 1987;Rasschaert & Laude, 1987;de Groot et al, 1987). However, Makino et al (1987) have localized neutralizing determinants to the carboxy-terminal one-third of the E2 protein for mouse hepatitis virus (MHV) by analysis of RNA recombinants with crosses within the gene encoding The aim of this study was to identify these determinants and begin to relate that information to the structure of the BCV E2 protein.…”
Section: Introductionmentioning
confidence: 99%